Importance Teachings About New Heaven and Earth - Benny Zakaria; Aprianus L. Moimau (International Journal of Christian Education and Philosophical Inquiry, 2024)
The second coming of Christ is an event inalienable to mankind. In addition to declaring punishment for unbelievers, His second coming also fulfills the presence of a new heaven and earth in which the righteous will reign with Christ forever. Of this, the Bible records that "the heavens shall vanish with a great rumbling, and the elements of the world shall burn in the flames, and the earth and all that is therein shall pass away." But on the other hand, the view of restoration clearly teaches that the old heavens and the earth will not be totally destroyed, but renewed. Thus the problem arises: how could both of these things - the biblical concept of the new earth and the doctrine of restoration - be a harmonious truth? This paper seeks to explain and discuss the problematic teaching of the restoration in relation to the concept of the new earth. Through this paper the author hopes to elaborate the problematic of this topic clearly, especially regarding the alleged contradictions that exist. In addition, critical analysis is conducted to produce responsible solutions that contribute significantly to the study of eschatology, in which the authors believe that the teaching of restoration and the concept of the new earth is a harmonious and biblical truth.